Variability of Expert Opinion in Treatment of Early-onset Scoliosis - Vitale, Michael G. (Springer-Verlag, 2010)
BACKGROUND: In contrast with treatment recommendations for adolescent idiopathic scoliosis, there are no clear algorithms for treating patients with early-onset scoliosis. There has been rapid expansion of treatment options for children with early-onset scoliosis, including casting, growth rods, the vertical expandable prosthetic titanium rib, and anterior vertebral stapling. QUESTIONS/PURPOSES: Given the range of treatment options, we assessed variability in decision making regarding treatment of patients with early-onset scoliosis. METHODS: We presented 12 clinical and radiographic vignettes about patients with early-onset scoliosis to 13 experienced spine surgeons who are members of the Chest Wall and Spine Deformity Study Group. The reviewers were asked to choose type of treatment, type of construct, construct location, and whether a thoracotomy should be performed. RESULTS: All 13 surgeons agreed regarding the need for surgery in eight of the 12 cases. When the reviewers chose surgery, 76% (40%–100%) selected the vertical expandable prosthetic titanium rib; of those selecting that approach, 61% (0%–100%) coincided on using it bilaterally. Agreement was 20% (0%–60%) for growing rods and 4% (0%–25%) for fusions. Among all cases, agreement regarding whether instrumentation should extend to the pelvis was 71% (50%–100%). In all but two cases, at least 85% of surgeons recommended against a thoracotomy. CONCLUSIONS: Although most surgeons agreed about the indication for surgery, we found wide variability in choice of construct type, number of constructs, and level of instrumentation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11999-010-1540-0) contains supplementary material, which is available to authorized users.